Extrudate swell of linear and branched polyethylenes: ALE simulations and comparison with experiments - Ganvir, Vivek; Gautham, Basavarsu P.; Pol, Harshawardhan; Bhamla, M. Saad; Sclesi, Lino; Thaokar, Rochish; Lele, Ashish K.; Mackley, Malcolm (Journal of Non-Newtonian Fluid Mechanics, 2011)
Extrudate swell is a common phenomenon observed in the polymer extrusion industry. Accurate prediction of the dimensions of an extrudate is important for appropriate design of dies for profile extrusion applications. Prediction of extrudate swell has been challenging due to (i) difficulties associated with accurate representation of the constitutive behavior of polymer melts, and (ii) difficulties associated with the simulation of free surfaces, which requires special techniques in the traditionally used Eulerian framework. In a previous work we had argued that an Arbitrary Lagrangian Eulerian (ALE) based finite element formulation may have advantages in simulating free surface deformations such as in extrudate swell. In the present work we reinforce this argument by comparing our ALE simulations with experimental data on the extrudate swell of commercial grades of linear polyethylene (LLDPE) and branched polyethylene (LOPE). Rheological behavior of the polymers was characterized in shear and uniaxial extensional deformations, and the data was modeled using either the Phan-Thien Tanner (PTT) model or the eXtended Pom-Pom (XPP) model. Additionally, flow birefringence and pressure drop measurements were done using a 10:1 contraction-expansion (CE) slit geometry in a MultiPass Rheometer. Simulated pressure drop and contours of the principal stress difference were compared with experimental data and were found to match well. This provided an independent test for the accuracy of the ALE code and the constitutive equations for simulating a processing-like flow. The polymers were extruded from long (L/D=30) and short (L/D=10) capillaries dies at 190 degrees C. ALE simulations were performed for the same extrusion conditions and the simulated extrudate swell showed good agreement with the experimental data. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: ALE-FEM; extrudate swell; Flow birefringence; MultiPass Rheometer; PSD; PTT; XPP

Extrusion film casting of long chain branched polypropylene - Chikhalikar, Kalyani; Banik, Sourya; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Doshi, Pankaj; Pol, Harshawardhan; Lele, Ashish K. (Polymer Engineering and Science, 2015)
Extrusion film casting (EFC) is an important melt processing operation which is extensively used to make polypropylene (PP) films. Linear PP shows significant amount of necking and draw resonance during EFC. One of the ways to reduce necking is to introduce long chain branches (LCB) on the polymer backbone. The long branches impart extensional strain hardening behavior thereby stabilizing the melt flow. In this work, we investigate the influence of long chain branching in polypropylene on the extent of necking in the EFC process. Laboratory scale EFC experiments were performed on homopolymer PP of linear and long chain branched architectures. Simulations of the EFC process were carried out using the one-dimensional flow model of Silagy et al., Polym. Eng. Sci.,36, 2614 (1996) into which we incorporate two different multi-mode molecular constitutive equations namely, the eXtended Pom-Pom' equation (XPP, for long chain branched PP) and the Rolie-Poly' equation (RP-S, for linear PP). Our experimental data confirm that presence of long chain branching in PP reduces the extent of necking and our numerical predictions show qualitative agreement with experimental data, thereby elucidating the role of chain architecture on the extent of necking. POLYM. ENG. SCI., 55:1977-1987, 2015. (c) 2014 Society of Plastics Engineers

Effect of plug temperature on the strain and thickness distribution ofcomponents made by plug assist thermoforming - Marathe, D.; Rokade, D.; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Gupta, S.; Kulkarni, S.; Juvekar, Vinay A.; Lele, Ashish K. (International Polymer Processing, 2016)
Plug temperature is a key parameter affecting the thickness distribution of thermoplastic components made by plug assist thermoforming. For a specified pair of plug and plastic sheet, the variation in plug temperature can alter the coefficient of friction (COF) between the pair. We show here how the temperature dependence of COF influences the nature and extent of biaxial stretching of the sheet and consequently the thickness distribution of the thermoformed component. In the present study, high impact polystyrene (HIPS) sheets were thermoformed into axisymmetric cups using a plug-assist process in which the aluminum plug temperature (T-plug) was varied from ambient to above the glass transition temperature of HIPS (similar to 100 degrees C). Biaxial strain maps on the surfaces of the formed cups were measured and quantified using Grid Strain Analysis (GSA). Thickness distributions of the cups were also measured. Temperature dependent COF between HIPS and aluminum was determined independently using a rotational rheometer. The measured COF was low for T < 100 degrees C, whereas it increased appreciably at and above 100 degrees C. We conclude that when T-plug < 100 degrees C the HIPS sheet slips on the plug during forming, and this results in biaxial stretching of the base and walls of the formed cup. In contrast for T-plug > 100 degrees C, a significant reduction in the magnitude of slip is expected. Here the sheet is gripped at the clamp and by the plug during forming which causes reduced biaxial stretching of the base and increased uniaxial stretching of the walls of the cup. Simulations of plug-assist thermoforming using a temperature dependent COF showed qualitative agreement with the GSA data thereby supporting our inferences.

Enhancing thermomechanical and chemical stability of polymer electrolyte membranes using polydopamine coated nanocellulose - Ram, Farsa; Velayutham, Parthiban; Sahu, Akhila Kumar; Lele, Ashish K.; Shanmuganathan, Kadhiravan (ACS Applied Energy Materials, 2020)
We report here an approach to enhance the chemical and thermomechanical stability of polymer electrolyte membranes without compromising proton conductivity. Multifunctional polydopamine coated nanocellulose (PNC) was prepared by oxidative polymerization of dopamine on nano cellulose fibers and subsequently incorporated in Nafion by solution blending. PNC had a very significant effect on the thermomechanical properties of Nafion showing up to 200% improvement in the storage modulus at 90 degrees C. The PNC network also enhanced the dimensional stability of Nafion under constant stress. The 3 wt % PNC composite membrane showed a drastic reduction in creep compliance of about 39.9% and 46.5% in J(max) at 30 degrees and 60 degrees C, respectively. Free radical scavenging properties of polydopamine also helped to significantly enhance the chemical stability of Nafion, which was ascertained by accelerated degradation tests conducted in Fenton's reagent at 70 degrees C over 40 days. F-19 CP MAS solid state NMR, FTIR, and tensile tests on the membranes show higher chemical stability of the 3 wt % PNC composite membrane. The proton conductivity of the 3 wt % PNC composite membrane at 90 degrees C and 100% RH (similar to 125 mS/cm) was slightly higher than the Nafion membrane (similar to 94 mS/cm) at similar conditions. The retention of proton conductivity even with lower water uptake could be ascribed to proton hopping through polydopamine coated nanocellulose. Performance of the composite membrane was also evaluated in a single stack fuel cell and found to be better than recast Nafion. The benefits derived by this approach are not restricted to Nafion alone and shall broadly apply to many other polymer membranes.
Keywords: cellulose nanofibers; chemical stability; dimensional stability; fuel cell; polydopamine; polymer electrolyte membrane